2018
DOI: 10.1097/md.0000000000012510
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of heart rate variability in women with polycystic ovary syndrome

Abstract: We aimed to compare the modulation of the autonomic nervous system (ANS) in women with polycystic ovary syndrome (PCOS) with that in healthy ovulatory women on the basis of heart rate variability (HRV), and to analyze the characteristics of the ANS in PCOS.In a retrospective chart review, HRV, body mass index, and physical examination data in women with PCOS and those with regular menstrual cycles were collected. Approval from the institutional review board (IRB) was obtained (IRB No. 2017-05-007-001) for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…However, it is worth noting that rMSSD, which reflects parasympathetic modulation of HRV, exhibited a reduction in the cases studied. The results presented here align with the findings reported by Ji et al (2018) [24]. Yildirir et al [25] observed a decrease in high frequency (HF) and an increase in low frequency (LF) in individuals with polycystic ovary syndrome (PCOS) compared to the control group.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, it is worth noting that rMSSD, which reflects parasympathetic modulation of HRV, exhibited a reduction in the cases studied. The results presented here align with the findings reported by Ji et al (2018) [24]. Yildirir et al [25] observed a decrease in high frequency (HF) and an increase in low frequency (LF) in individuals with polycystic ovary syndrome (PCOS) compared to the control group.…”
Section: Discussionsupporting
confidence: 92%
“…Studies have incorporated the COMPASS-31 scale in the assessment of diabetic autonomic neuropathy (DAN), cardiac autonomic neuropathy (CAN), SFPNs, etc. [24].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, Sverrisdóttir et al found increased sympathetic nerve activity in patients with PCOS by direct measurement [ 12 ]. Other authors obtained similar results using the heart rate variability for indirect evaluation of autonomous function [ 13 , 14 ]. However, few studies have investigated the plasma levels of catecholamines and their metabolites in PCOS patients with somewhat contradictory results [ 15 17 ].…”
Section: Introductionsupporting
confidence: 61%
“…In comparison between subgroup 1 and subgroup 2, pulse rate and respiratory rate are more important features in subgroup 1 in Figure 16 , and AMH is a more important feature (also note that the SHAP values of AMH are more spread out) in subgroup 2 than in the other subgroup, as shown in Figure 17 . Regarding pulse rate and respiratory rate being important in subgroup 1, heart rate variability in normal weight women with PCOS has been subject to debate in the literature [ 35 , 36 ].…”
Section: Resultsmentioning
confidence: 99%